2019
DOI: 10.1371/journal.pntd.0007146
|View full text |Cite
|
Sign up to set email alerts
|

The role of TLR9 on Leishmania amazonensis infection and its influence on intranasal LaAg vaccine efficacy

Abstract: Leishmania (L . ) amazonensis is one of the etiological agents of cutaneous leishmaniasis (CL) in Brazil. Currently, there is no vaccine approved for human use against leishmaniasis, although several vaccine preparations are in experimental stages. One of them is Leishvacin, or LaAg, a first-generation vaccine composed of total L . amazonensis antigens that has consistently shown an increase of mouse resistance against CL when admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Susceptibility is marked with larger lesion and increased parasite burden during chronic stage infection due to decreased IFNγ production in infected tissue as well as increased IgG production. 99 Taken together, the result of this study suggests that TLR9 contributes to C57BL/6 mice resistance to L. amazonensis infection. However, TLR9 signalling can promote progression of cutaneous lesions as well as promote intracellular survival of L. amazonensis by inducing the expression of CD200, a ligand known for suppressing pro-inflammatory cytokines production by macrophages.…”
Section: Role Of Tlr9 In L Amazonensis Infectionsupporting
confidence: 57%
“…Susceptibility is marked with larger lesion and increased parasite burden during chronic stage infection due to decreased IFNγ production in infected tissue as well as increased IgG production. 99 Taken together, the result of this study suggests that TLR9 contributes to C57BL/6 mice resistance to L. amazonensis infection. However, TLR9 signalling can promote progression of cutaneous lesions as well as promote intracellular survival of L. amazonensis by inducing the expression of CD200, a ligand known for suppressing pro-inflammatory cytokines production by macrophages.…”
Section: Role Of Tlr9 In L Amazonensis Infectionsupporting
confidence: 57%
“…Many studies have shown the importance of TLR9, a receptor of the TLR family, in fungal infections, mainly in models of infection by Aspergillus fumigatus 28 , Candida albicans 29 and Cryptococcus neoformans 30,31 . TLR9 is found in endosomal vesicles and capable of recognizing fractions of non-methylated DNA, which are common in viruses, prokaryotes and some protozoa, such as those of the genus Leishmania 32,33 . TLR9 is located in endoplasmic reticulum and is translocated to the lysosome and Golgi complex after direct interaction with CpG motifs present in single-stranded DNA (ssDNA).…”
mentioning
confidence: 99%
“…In this context, TLR4, which can also be activated by LPG, is associated with both NO and TNF production following in-vitro macrophage infection ( 104 , 105 ). The role played by TLR9 is controversial, L.a. amastigotes can release DNA on micro-vesicles, activating endosomal TLR9, which required both Myd88 and TRIF to induce CD200, which blocks iNOS expression, resulting in a transient higher resistance in TLR9 -/- mice compared to Wt mice, in early but not chronic phases of the disease ( 106 , 107 ). Lastly, the expression of TLR2, TLR4 and TLR9 is different during different clinical manifestations of L.a. infection in humans.…”
Section: The Initial Events: Leishmania -Phagocyte Interactionsmentioning
confidence: 99%